2015
DOI: 10.1515/ijfe-2014-0314
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Genipin-Crosslinked Chitosan Microspheres for the Sustained Release of Salidroside

Abstract: Chitosan microspheres (CsMs) that encapsulate salidroside (Sal) were prepared by the emulsion crosslinking method with naturally occurring genipin (Gp) and then examined for their in vitro release. Sal-loaded CsMs (Sal-CsMs) showed nearly spherical and smooth surfaces with internal voids. The particle size of Sal-CsMs ranged within 0.56-5.01 μm, and their encapsulation efficiency and loading capacity were beyond 77.58% and 23.29%, respectively. The stability of Sal improved after entrapment into the CsMs. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…The studies by Luo et al (2015), showed when preparing chitosan microspheres by the emulsion crosslinking method using genipin (Gp) for in vitro studies of controlled release of salidroside and Zhang et al (2011), when carrying out a comparative investigation regarding the intestinal absorption of the inclusion complex genipin/hydroxypropyl-β-cyclodextrin (HP-β-CD) with that of genipin, they also observed the same characteristic peaks in the X-ray diffraction of genipin.…”
Section: Resultsmentioning
confidence: 87%
“…The studies by Luo et al (2015), showed when preparing chitosan microspheres by the emulsion crosslinking method using genipin (Gp) for in vitro studies of controlled release of salidroside and Zhang et al (2011), when carrying out a comparative investigation regarding the intestinal absorption of the inclusion complex genipin/hydroxypropyl-β-cyclodextrin (HP-β-CD) with that of genipin, they also observed the same characteristic peaks in the X-ray diffraction of genipin.…”
Section: Resultsmentioning
confidence: 87%
“…The salidroside stability was improved after being entrapped into chitosan microspheres. The release rate of salidroside from chitosan microspheres was rapid initially, followed by controlled release 276 . Improved stability and controlled release of salidroside were also achieved through incorporation of salidroside into polymer network microspheres prepared by chitosanand methylcellulose 277 …”
Section: Approaches To Improve the Bioavailability Of Phgsmentioning
confidence: 99%
“…The release rate of salidroside from chitosan microspheres was rapid initially, followed by controlled release. 276 Improved stability and controlled release of salidroside were also achieved through incorporation of salidroside into polymer network microspheres prepared by chitosanand methylcellulose. 277 To enhance the intestinal absorption and oral bioavailability, echinacoside-phospholipid complex was prepared.…”
mentioning
confidence: 99%
“…Chitosan possesses excellent film-forming ability and is suitable for the formulation of edible films. Chitosan film is a convenient packaging material, and its different forms, such as composite, modified and sustainedrelease chitosan films have been extensively investigated (Luo et al 2015;Pranoto et al 2005). Chitosan films are used to reduce water vapour, oxygen, lipid and flavour migration between components of multi-component food products, and compositing is one of the useful methods to append functional properties to chitosan films (Rao et al 2010).…”
Section: Introductionmentioning
confidence: 99%